2003
DOI: 10.1042/bj20020981
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor alpha (PPARalpha)-mediated regulation of multidrug resistance 2 (Mdr2) expression and function in mice

Abstract: Peroxisome proliferator-activated receptor alpha (PPARalpha) is a nuclear receptor that controls expression of genes involved in lipid metabolism and is activated by fatty acids and hypolipidaemic fibrates. Fibrates induce the hepatic expression of murine multidrug resistance 2 ( Mdr2 ), encoding the canalicular phospholipid translocator. The physiological role of PPARalpha in regulation of Mdr2 and other genes involved in bile formation is unknown. We found no differences in hepatic expression of the ATP bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
118
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 57 publications
12
118
1
2
Order By: Relevance
“…Some studies suggest both PPAR-␣ and PPAR-␥ activate ABCA1 expression indirectly by enhancing the transcription of LXR-␣, the promoter of which contains a PPRE (13,16,49,90). A recent study, however, found no change in liver ABCA1 mRNA levels in PPAR-␣ knockout mice (48). While additional studies are required, these findings lend further support for the use of synthetic PPAR as well as LXR or RXR agonists in the prevention or treatment of atherosclerosis.…”
Section: Ppar-␣ Effects On Tg Ldl and Hdl Metabolismmentioning
confidence: 61%
“…Some studies suggest both PPAR-␣ and PPAR-␥ activate ABCA1 expression indirectly by enhancing the transcription of LXR-␣, the promoter of which contains a PPRE (13,16,49,90). A recent study, however, found no change in liver ABCA1 mRNA levels in PPAR-␣ knockout mice (48). While additional studies are required, these findings lend further support for the use of synthetic PPAR as well as LXR or RXR agonists in the prevention or treatment of atherosclerosis.…”
Section: Ppar-␣ Effects On Tg Ldl and Hdl Metabolismmentioning
confidence: 61%
“…[35][36][37] However, these compounds may induce other hepatic injury and have considerable side effects. 38 In conclusion, our data indicate that toxic bile composition, because of a high biliary bile salt/phospholipid ratio, acts synergistically to ischemia/reperfusion injury in the origin of bile duct injury after OLT. Bile salts aggravate the cold ischemia/reperfusion injury of the bile ducts, initiating an inflammatory cell invasion, cholestasis, and bile duct proliferation.…”
Section: Discussionmentioning
confidence: 92%
“…PPAR-␣ agonists were recently shown to stimulate Mdr2 overexpression, 44 suggesting that this finding could rather be related to the PPAR-␣-activating capacity of atorvastatin. 22 Because an imbalance in the biliary phospholipid and bile acid ratio in Mdr2 knockout mice leads to a cholestatic phenotype resembling primary sclerosing cholangitis, 15,17 it is attractive to speculate that induction of Mdr2 and biliary phospholipid secretion by statins might protect bile ducts against toxic bile acids.…”
Section: Discussionmentioning
confidence: 99%